Ranking Rate Control and Rhythm Control Therapies for Heart Failure Patients With Atrial Fibrillation: A Network Meta-Analysis of Randomized Controlled Trials - Zhang, Cong; Luo, Hongxing; Xu, Yu; Wang, Juntao; Shi, Yanan; Zhang, Pengfei (Cardiology and Cardiovascular Medicine, 2018)
Background: Rate control and rhythm control have demonstrated similar benefits for heart failure (HF) patients with atrial fibrillation (AF), but no study has attempted to rank their benefits. We aim to conduct a network metaanalysis of the efficacies of rate control and rhythm control therapies for HF patient with AF. Methods: We searched PubMed, Embase, and Cochrane Library with various combinations of “rate control”, “rhythm control”, “atrial fibrillation” and “heart failure”. The retrieved records were screened by “Patient- Intervention-Control-Outcome” principle. The eligible randomized controlled trials were extracted for basic characteristics, outcomes data, and synthesized with random-effects model. Results: Eleven trials involving 2,086 patients and 8 rate control and rhythm control therapies were included. The interventions for all-cause mortality reduction were ranked as follows: catheter ablation (mean rank [MR] 2.3, surface under the cumulative ranking curves [SUCRA] 81.1%), atrioventricular node ablation and pacemaker (MR 3.1, SUCRA 70.0%), β-blocker (MR 3.9, SUCRA 58.8%), optimal medical treatment (MR 3.9, SUCRA 57.9%), amiodarone (MR 4.3, SUCRA 52.9%), placebo (MR 4.5, SUCRA 50.3%), digoxin (MR 6.8, SUCRA 16.7%), β- blocker and/or digoxin (MR 7.1, SUCRA 12.2%). Conclusion: In HF patients with AF, catheter ablation may be the most effective therapy for rate control and rhythm control, while digoxin is probably harmful.